INFLUENCE OF BIFUNCTIONAL LYOPHILIC MODIFIER ON DIELECTRIC PROPERTIES OF POLYURETHANE LACQUER WATERBORNE EMULSION - Фабуляк, Ф.Г.; Таран, Т.В.; Ульянкіна, Д.С. (Proceedings of National Aviation University (archive), 2012)
The main positive properties of polyurethane have been studied. References to methods to modify them are given. Shown the possibility of regulating the properties of polyurethane water dispersions by modifying polymer by ethylene glycol.